LEMMATIZING TEXTBOOK CORPUS FOR LEARNER DICTIONARY OF BASIC VOCABULARY - Astika, Gusti (Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to lemmatize the vocabulary used in textbooks with the purpose to provide information for dictionary entries that are relevant to the learners.Â Although dictionaries for learners are commercially and electronically available, they may not be relevant to the learnersâ€™ needs for vocabulary learning in class, or may not have been designed for specific pedagogical purposes. To bridge this gap, the vocabulary used in some textbook series were analyzed using the vocabulary profiler available in Lextutor.com to identify the lemmas of different frequency levels. The analysis shows that the total number of lemmas in the textbooks were approximately about 58% of the total number of the most frequently used lemmas in the New General Service List (Browne, Culligan, Phillips, 2013). Further exploration of the lexicogrammatical environment in the textbook corpus discovered lexical items that behave differently with regard to functions and meanings. These findings should provide lexicographers or teachers with useful information about word entries for a relevant learner dictionary to be used in the classroom.